The use of self-compassion techniques in elite footballers: mistakes as opportunities to learn. (10th October 2022) - James, I. A.; Medea, B.; Harding, M.; Glover, Danny; Carraça, B.
Abstract: Mistakes made by players during a game are common in football, and when handled well they provide opportunities to learn and develop skills. However, when there is excessive self-criticism associated with the error, leading to dysfunctional cognitions about the self, there is the potential for a reduction in performance and wellbeing. Self-criticism can serve a number of functions but when it is excessive and undermines a player's sense of adequacy and self-esteem it can lead to anxiety and depression. The current article explores the use of self-compassion techniques as methods for reducing the potential negative impacts of self-criticism. This paper is a narrative review of the literature, examining the theory and evidence base associated with the use of self-compassion approaches in sport, particularly football. The article presents protocols used with professional footballers to promote performance and wellbeing. Key learning aims: (1) Elite athletes are prone to a range of mistakes and stressors, sport and non-sport related, that they are required to deal with in order to maintain their performance and wellbeing. (2) Self-compassion strategies are useful techniques for elite athletes to both help maintain wellbeing and prevent the occurrence of 'mental health symptoms'. (3) Evidence suggests that self-compassion strategies are helpful to footballers, and beneficial protocols have been used in studies with professional footballers.